PENGARUH KUALITAS PELAYANAN, HARGA, DAN CITRA TERHADAP KEPUASAN KONSUMEN - M, Mugiatin; Jayanti, Esih; Werdiasih, Rustina Dewi (JURNAL EKONOMI, 2024)
This study aims to test and analyze The Effect of Service Quality, Price, and Image on ConsumerSatisfaction (Case Study at Alumni of Ganesha Operation Tutoring Institute in Cilacap City). Data collection was carried out by distributing questionnaires to 100 respondents. The sampling technique in this study used technique purposive sampling. Data analysis techniques used, including validity tests; reliability tests; MSI (Method of Successive Interval); classical assumption tests including linearity tests, normality tests, multicollinearity tests, and heteroscedasticity tests; multiple linear regression analysis; hypothesis tests including t-tests and F tests; and coefficient of determination analysis (R2). The analysis results showed that the quality of service did not significantly affect customersatisfaction at the Ganesha Operation Cilacap Tutoring Institute with a significance value = 0.618 > 0.05. Price positively and significantly affects consumer satisfaction with a significance value = 0.000 < 0.05. Image has a positive and significant effect on consumer satisfaction with a significance value = 0.001 < 0.05. Service quality, price, and image simultaneously positively affect customer (student) satisfaction at the Ganesha Operation Cilacap Tutoring Institute with a significance value = 0.000 < 0.05.